Effects of Oil Drops and the Charcoal’s Proximate Composition on the Air Pollution Emitted from Charcoal Barbecues - Kuo-Pin Yu; Yen-Chi Chen; Yun-Jhe Miao; Sepridawati Siregar; Yu Wei Tsai; Whei-May Grace Lee (Aerosol and Air Quality Research)
Abstract This research investigated the emission rates (ERs) and emission factors (EFs) of air pollutants generated from charcoal barbecues and the influence of temperature, the charcoal’s proximate composition (moisture, volatile matter, fixed carbon, and ash), and oil drops. Charcoal briquettes, longan charcoal, and binchotan (commonly used for indoor barbecues) were selected for combustion experiments, and the exhaust gas was collected for the analysis of air pollutants, viz., CO, CO2, NOx, hydrocarbons (HCs), benzene, toluene, formaldehyde, acetaldehyde, PM2.5, and trace metals (Al, Cr, Cu, Fe, and Zn). A linear regression model was employed to verify the major factors affecting the EFs. The EFs of HCs measured during the dripping of oil and sauce on the charcoal ranged from 2486.2 to 9305.2 mg kg−1, 76.4–357% higher than those measured during no dripping. For PM2.5, the EFs measured during dripping ranged from 3080.4 to 3926.5 mg kg−1, 8–19 times higher than those measured during no dripping. The EFs of benzene, toluene, formaldehyde, and acetaldehyde also significantly increased during dripping. In addition, increasing the combustion temperature reduced the EFs of HCs, formaldehyde, and CO but increased those of Fe and Zn. The charcoal moisture content was significantly positively correlated with the EF of HCs, whereas the volatile matter content was significantly positively correlated with those of HCs and benzene. Positive correlations existed between the charcoal ash content and the EFs of CO, Fe, and Zn. The fixed carbon content was significantly positively correlated with the EF of CO2 but negatively correlated with those of CO, Al, and Zn.